INTEGRATING APPRENTICESHIPS WITHIN HIGH SCHOOLS IN THE UNITED STATES TO DRIVE A STRONGER WORKFORCE - Thurston, Jordan (Digital Repository of Theses, 2023)
Whether attributed to The Great Resignation, COVID-19, or general unemployment in the United States, organizations need to widen their scope for attracting top talent to stay competitive. With the job market estimated to increase by 11.9 million from 2020 to 2030, organizations need to rethink how and where they recruit new talent to fill these positions, which involves looking at a new market. High School graduates are an untapped market of knowledge, perspectives, and drive that organizations should be aware of. Through this thesis, I want to study and present new data and demonstrate a positive impact on the macro and micro economy when school districts partner with organizations to provide apprenticeships to high school students by assessing the direct economic and employment impact. This is to help address management concerns about hiring and retaining talent to tackle current labor shortages. Surveying a sample of high school students and school districts in the United States will depict a clearer picture of education’s impact on the workforce and give organizations another talent pool for hiring.